Mathematical model of inverted analemmatic sundial on the example of Belogorsk sundial of the Bronze Age - Vodolazhskaya, L.N. (Archaeoastronomy and Ancient Technologies, 2022)
This article proposes a mathematical model of an inverted analemmatic sundial, provides formulas for calculating the coordinates of their hour markers. On the example of the Belogorsk sundial, a method is described for determining the accuracy of time measurement using an inverted analemmatic sundial, in which cup marks are used as hour markers. The obtained value of the accuracy of time measurement with the help of the Belogorsk sundial is 5÷6 minutes and is quite good for a measuring instrument of the Bronze Age, and is also higher than the accuracy of time measurement with the help of a water clock. As a result, it is concluded that the hypothesis is confirmed that the invention of the sundial was associated with the need to improve the accuracy of time measurement using a water clock.